1990
DOI: 10.2307/1243143
|View full text |Cite
|
Sign up to set email alerts
|

Utilization, Profitability, and the Adoption of Animal Draft Power in West Africa

Abstract: Farmers in West Africa's semi‐arid tropics have been slow to adopt animal draft power to replace manual cultivation, defying the logic of conventional choice‐of‐technique analyses. This paper demonstrates that farmers can profitably adopt animal draft power when household characteristics and exogenous factors permit high utilization of animals and equipment. Empirical analysis of farm‐level data indicates that low utilization is the key cause of low returns, and that a long learning period precedes achieving h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Agriculture and food (Babu et al, 2000), (Badini et al, 2007), (Bakker et al, 1998), (Bontkes and van Keulen, 2003), (Bosma et al, 1999), (Brossier and Jager, 1984), (Cabanilla et al, 2005), (Delgado and McIntire, 1982), (Dijk, 1997), (Groot and Coulibaly, 1994), (Haefele et al, 2003), (Hengsdijk and van Ittersum, 2002), (Hengsdijk and van Ittersum, 2003), (Hyman, 1991), ( Jaeger and Matlon, 1990), (Kaya et al, 2000), (Kruseman and Bade, 1998), (Langyintuo et al, 2005), (Roncoli et al, 2007), (Samake´, 2003), (Staatz et al, 1989), (Van Duivenbooden, 1993), (Van Duivenbooden, 1999), (Van Duivenbooden and Veeneklaas, 1993), (Vitale and Sanders, 2005). Agriculture and food (Babu et al, 2000), (Badini et al, 2007), (Bakker et al, 1998), (Bontkes and van Keulen, 2003), (Bosma et al, 1999), (Brossier and Jager, 1984), (Cabanilla et al, 2005), (Delgado and McIntire, 1982), (Dijk, 1997), (Groot and Coulibaly, 1994), (Haefele et al, 2003), (Hengsdijk and van Ittersum, 2002), (Hengsdijk and van Ittersum, 2003), (Hyman, 1991), …”
Section: Malimentioning
confidence: 99%
See 1 more Smart Citation
“…Agriculture and food (Babu et al, 2000), (Badini et al, 2007), (Bakker et al, 1998), (Bontkes and van Keulen, 2003), (Bosma et al, 1999), (Brossier and Jager, 1984), (Cabanilla et al, 2005), (Delgado and McIntire, 1982), (Dijk, 1997), (Groot and Coulibaly, 1994), (Haefele et al, 2003), (Hengsdijk and van Ittersum, 2002), (Hengsdijk and van Ittersum, 2003), (Hyman, 1991), ( Jaeger and Matlon, 1990), (Kaya et al, 2000), (Kruseman and Bade, 1998), (Langyintuo et al, 2005), (Roncoli et al, 2007), (Samake´, 2003), (Staatz et al, 1989), (Van Duivenbooden, 1993), (Van Duivenbooden, 1999), (Van Duivenbooden and Veeneklaas, 1993), (Vitale and Sanders, 2005). Agriculture and food (Babu et al, 2000), (Badini et al, 2007), (Bakker et al, 1998), (Bontkes and van Keulen, 2003), (Bosma et al, 1999), (Brossier and Jager, 1984), (Cabanilla et al, 2005), (Delgado and McIntire, 1982), (Dijk, 1997), (Groot and Coulibaly, 1994), (Haefele et al, 2003), (Hengsdijk and van Ittersum, 2002), (Hengsdijk and van Ittersum, 2003), (Hyman, 1991), …”
Section: Malimentioning
confidence: 99%
“…(Bollou, 2006), (Ngwenyama et al, 2006). (Barbier, 1998), (Barbier et al, 2004), (Delgado and McIntire, 1982), (Freidberg, 1997), (Ingramand et al, 2002), (Jaeger and Matlon, 1990), (Langyintuo et al, 2005), (Maatman, 2000), (Maatman et al, 2002), (Noordwijk et al, 1995), (Roth et al, 1990), (Sanders et al, 1990), (Schweigman et al, 1998), (Zimmerman and Carter, 1999), (Zimmerman and Carter, 2003), (Zougmore´, 2003). , 2002), ( Paxton et al, 2000).…”
Section: Cross-referencesmentioning
confidence: 99%
“…Previous research on agricultural mechanization for West Africa as a whole has focused largely on innovations for providing draft-power such as animal and tractor power (Bobboi, 1997;Delgado and McIntire, 1982;Jaeger and Malton, 1990). The only published study on farm mechanization in Ghana was a comparative analysis of hoe and bullock draft-power farming (Panin, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies on innovative farm mechanization initiatives for subSaharan Africa have reported low adoption rates (Degaldo and McIntire, 1982;Jaeger and Malton, 1990;Sargent et al, 1981) or high abandonment of many projects (Degaldo, 1979;Le Moigne, 1979;Panin, 1988) partly because the recommended packages did not adequately address key adopter issues and problems (Crawford and Lassiter, 1985;Lele, 1975;Sargent et al, 1981). Furthermore, variability in ethnographic and economic conditions, as well as differences in agro-ecological zones, each with unique farm management requirements, suggest that identical forms of farm mechanization would likely not suit all agro-ecological regions.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large literature on the adoption of agricultural technologies (Doss, ; Feder et al., ; Lee, ; Pattanayak et al., ), most often estimating the probability of adopting a new practice as a function of human capital (Asfaw and Admassie, ; Caviglia and Kahn, ; Herath and Takeya, ) and economic constraints (Fearnside and Alencastro Graça, ; Jaeger and Matlon, ; Kebede et al., ; Rahm and Huffman, ; Soule, Tegene and Wiebe, ). However, relatively few studies have modeled continued use of these practices over time with panel data (Doss, ; Wendland and Sills, ).…”
Section: Introductionmentioning
confidence: 99%